Spatial Dynamics of Digital Society Index in Indonesia: A Spatial Autoregressive Approach - Zakiyah Mar'ah; H. S., Rahmat; Hidayat, Rahmat (Jurusan Matematika FMIPA UNM, 2025)
The equitable distribution of digital transformation in Indonesia is a strategic issue, given the importance of technology in supporting national development. Indeks Masyarakat Digital Indonesia (IDSI) or Indonesian Digital Society Index (IDSI) was developed to measure the level of digital literacy, inclusion, and digital infrastructure readiness at the provincial level. However, the distribution of IDSI values shows striking spatial disparities. This research aims to identify spatial dependency patterns and significant factors influencing IDSI using a Spatial Autoregressive (SAR) model. The data used is the 2024 IDSI from 34 provinces in Indonesia, with five independent variables: access and adoption of digital technology, learning ecosystem, ICT introduction, empowerment, and employment. A spatial autocorrelation test using Moran's I revealed a significant positive spatial dependency, indicating a clustered pattern in IDSI distribution. The Lagrange Multiplier test showed spatial dependency in the lag or response variable, making the SAR model suitable. Estimation results demonstrate that all five independent variables significantly impact IDSI, with a coefficient of determination (R²) of 0.98. These findings indicate that geographically proximate regions tend to have similar IDSI values. Therefore, spatial approaches like SAR are crucial for formulating national digital equity policies.